Seminaire Bourbaki, volume 1998/99, exposes 850-864 - Seminaire Bourbaki; Seminaire Bourbaki , 1998/99 (Paris Societe Mathematique de France, 2000)
As in the preceding volumes of this seminar, one finds here fifteen survey lectures on topics of current interest : two lectures on theory of Lie groups and algebras, one of algebraic geometry, three on p-adic arithmetical algebraic geometry, one on combinatorial geometry, one on differential geometry, two on partial differential equations, two on probabilities, one on celestial mechanics and one on quantum computing.
Keywords: Algebraic geometry; Differential equations; Lie groups